Internationalisation and market entry modes and strategies : the literature state of the art. - Choong, Esther Wan Chin. (2008)
The purpose of this study is to achieve an understanding of the immense amount of literature on foreign direct investment paying particular attention to the aspect of market. The research consists of a qualitative analysis of journal articles pertaining to foreigndirect investment and market entry mode.